Mamak dan Uang Jemputan dalam Novel "Mahar Cinta Gandoriah" - Rina Elvia; Khairil Anwar; Eka Meigalia (Jurnal Elektronik WACANA ETNIK, 2018)
This paper describes the tradition of uang japuik contained in the Mahar Cinta Gandoriah novel. Uang japuik is unique gift of a bride to a bridegroom. This tradition is still carried out even though it is difficult. Through negotiations and agreements, those problems can be overcome and continue in the next process. This uang japuik is usually given in goods, but some provide cash. Novel Mahar Cinta Gandoriah tells about the refusal of matchmaking because the uang japuik amount is too high. Also, in this novel, the role of mamak is not displayed properly.This study uses a qualitative method with structural and intertextual approach. As a result, the ideal mamak kandung must find a mate, maintaining customs, has responsibility  to niece. Besides, the intertextuality of the role of mamak and pick-up money in the Mahar Cinta Gandoriah novel is seen from the title, author and work, and the issue of the role of mamak and uang japuik.